A theoretical overview on the role of organizational citizenship behaviors in the promotion of innovation - LAMDAGHRI , Zidane; BENABDELHADI , Abdelhay (Revue Internationale des Sciences de Gestion, 2022)
The objective of this paper is to emphasize the importance of organizational citizenship behaviors (OCBs) in promoting innovation within organizations. Indeed, thanks to innovation, these organizations will be able to improve their performance and competitiveness. In order to deal with this important topic, we first reviewed the literature to identify the key definitions of OCBs. Then, we drew the most important dimensions of OCB. Moreover, we were able to identify the major outputs and impacts of OCBs. After that, we addressed innovation within organizations by presenting general definitions of this concept and its process’ main phases. Following these definitions, our research focused on identifying the main links and impacts of organizational citizenship behaviors on innovation. This allowed us to propose a model based on the analysis made by the main authors of these concepts. The model that we have proposed in this article can therefore be used in future studies related to our research. It is important to emphasize that this article aims to raise managers’ awareness of the major importance of OCBs on the improvement of innovation within their structures, thus allowing them to achieve gains in terms of performance as well as a better control of internal processes.